Analisis Pengaruh Pembayaran Non Tunai Terhadap Nilai Tukar Rupiah dengan Jumlah Uang Beredar sebagai Variable Intervening - Lusiana Anggraeni; Nugroho Sumarjiyanto Benedictus Maria (Diponegoro Journal of Economics, 2023)
This study aims to determine the impact of non-cash payments on the Rupiah exchange rate through the amount of money circulating in a narrow sense. This research is quantitative, utilizing secondary data as its source. The analytical method used in this study is path analysis, with the dependent variable being the Rupiah exchange rate. The independent variables are the volume of debit card transactions and the volume of electronic money, while the intervening variable is the amount of money circulating in a narrow sense. The period analyzed is from 2017 to 2020. The results show that both the volume of debit card transactions and the volume of electronic money have a significant effect on the Rupiah exchange rate. This study finds in the second model that the volume of debit card transactions, the volume of electronic money, and the Rupiah exchange rate significantly affect the amount of money circulating in a narrow sense.